Socioeconomic Influence on the Consumption Behavior of Land Kale (Ipomoea reptans) in Poasia District, Kendari City - Rani, Rani; Abdul Gafaruddin; Samsul Alam Fyka (International journal of technology and education research, 2024)
This study aims to determine (1) the socio-economic condition of consumption of land kale (Ipomoea Reptans) in Poasia District, Kendari City and (2) socioeconomic factors on the consumption behavior of land kale (Ipomoea Reptans) in Poasia District, Kendari City. The population in this study is all people who are consumers who have consumed land kale plants (Ipomoea Reptans). The sampling technique was carried out by accidental sampling. The number of samples taken was 60 people. The data analysis used in this study is descriptive statistics and multiple linear regression analysis. The results of this study are (1) The socio-economic condition of land kale consumers (Ipomoea Reptans) in Poasia District Kendari City consists of the number of family members in the high category, the level of education in the high category, the income in the very high category and the product price in the very high category and (2) cultural factors (X1 ) and psychological factors (X4 ) have a significant effect on the consumption behavior of land kale (Ipomoea Reptans) in the Poasia Landscape of Kendari City